Friend turned foe: E-cadherin perversely protects micrometastases - Wells, Alan; Ma, Bo (Translational Andrology and Urology; Vol 6, No 2 (April 29, 2017): Translational Andrology and Urology (Global Urology), 2017)
We thank Drs. Lin and Chuu for their recent insightful Commentary in TAU, on our paper in Hepatology concerning the role of E-cadherin in the survival and chemoresistance of prostate cancer metastases (1). We would like to take this opportunity to amplify or explain some of the findings as they discussed.